Baseline characteristics of the 4011 patients recruited into the 'Efficacy of Nitric Oxide in Stroke' (ENOS) trial. Issue 6 (9th July 2014) - ENOS Investigators; Bath, Philip M. W.; Adami, Alessandro; Bereczki, Daniel; Berge, Eivind; Beridze, Maia; Cala, Lesley; Casado, Ana; Caso, Valeria; Chang, Hui Meng; Christensen, Hanne; Collins, Ronan; et al.
<x xml:space="preserve">Abstract</x> Background High blood pressure is common in acute stroke and associated with a worse functional outcome. Many patients who present with acute stroke are taking prescribed antihypertensive therapy before their stroke. Aims ENOS tested whether lowering blood pressure and continuing pre‐stroke antihypertensive therapy are each safe and effective. Methods This study is an international multi‐centre prospective randomized single‐blind blinded‐endpoint parallel‐group partial‐factorial controlled trial of transdermal glyceryl trinitrate (a nitric oxide donor, given for seven‐days) vs. no glyceryl trinitrate, and of continuing vs. stopping (temporarily for seven‐days) pre‐stroke antihypertensive drugs if relevant, in patients with acute ischaemic stroke or intracerebral haemorrhage and high systolic blood pressure (140–220 mmHg). Results Recruitment ran from July 2001 to October 2013. Four thousand eleven patients [2097 (52·3%) in the continue/stop arm] were recruited from 173 sites across 23 countries in 5 continents (Asia 14%, Continental Europe 16%, UK 64%). Baseline characteristics include: mean age 70 (standard deviation 12) years; male 57%; mean time from stroke to recruitment 26 (13) h; mean severity (Scandinavian Stroke Scale) 34 (13) of 58; mean blood pressure 167 (19)/90 (13) mmHg; ischaemic stroke 83%; and intracerebral haemorrhage 16%. The main trial results will be presented in May 2014. The results will also be presented in updated Cochrane systematic reviews and included in individual patient data meta‐analyses of all relevant randomized controlled trials. Conclusion ENOS is a large completed international trial of blood pressure management in acute stroke and includes patients representative of many stroke services worldwide.